Antitubular Basement Membrane Antibody Disease Associated with Nivolumab Infusion and Concomitant Acute Pyelonephritis Leading to Acute Kidney Injury : a Case Report and Literature Review - Ahmad Oussama Rifai; Kristin M. Denig; Tiffany Caza; Shana M. Webb; Sarah Rifai; Sarah Khan; Sally Dahan; Samaa Alamin (Case Reports in Nephrology)
Antitubular basement membrane (anti-TBM) antibody disease is an extremely rare disorder. It may be idiopathic or secondary to exposure of the proximal tubular basement membrane, triggered by tubular injury due to acute pyelonephritis, acute allergic interstitial nephritis, or kidney allograft rejection. The histopathology of anti-TBM antibody disease is characterized by strong linear deposits of IgG with complement C3 along the proximal tubular cell basement membranes. The staining is restricted to proximal tubules. Currently, a kidney biopsy with these pathognomonic findings is the only diagnostic method. Serological testing and titers for anti-TBM antibodies are not clinically standardized. Our patient had pyelonephritis and possibly acute allergic interstitial nephritis as a result of nivolumab infusion. The kidney biopsy demonstrated dense interstitial infiltrates of neutrophil-rich interstitial inflammation, neutrophilic casts, and neutrophilic tubulitis consistent with acute pyelonephritis, as well as areas of mixed inflammation with lymphocytic tubulitis suggesting concurrent acute interstitial nephritis. The presence of linear IgG staining along proximal but not distal tubular basement membranes was diagnostic of anti-TBM antibody disease, favored to be due to both triggers. The patient was treated with discontinuation of nivolumab, intravenous antibiotics, and corticosteroids and was supported with hemodialysis. After 6 weeks, the patient’s kidney function recovered enough to discontinue hemodialysis and had significant renal improvement.